HUBUNGAN TINGKAT PENGETAHUAN WUS TERHADAP SIKAP MELAKUKAN DETEKSI DINI KANKER LEHER RAHIM DENGAN PEMERIKSAAN IVA DI PUSKESMAS PARE KECAMATAN KRANGGAN KABUPATEN TEMANGGUNG JAWA TENGAH - Rochayati, Anik (Universitas Muhammadiyah Surabaya, 2023)
Objective: The global cancer incidence is approaching a tipping point, with the incidence increasing year after year. Several factors, including women's level of knowledge, attitudes, and examination behavior, are thought to be related to the incidence of cervical cancer. In Temanggung Regency, the IVA examination achievement rate for women of childbearing age was only 5.34%, far below the Central Java target of 10%. (BPS, 2021).Methods: This study aims to determine the relationship between women of childbearing age's knowledge and attitudes toward early detection of cervical cancer with IVA at Pare Primary Health Center in Kranggan District, Temanggung. This study employed a cross-sectional approach to correlative analytic research. The research sample consisted of 37 women of childbearing age who were examined with a measuring instrument in the form of a questionnaire. Accidental Sampling was used in the data collection technique. The questionnaire method was used to collect data. The data processing technique used was Chi Square test.Results: The knowledge of the majority of Women of Reproductive Age was good, with as many as 23 respondents (62.2%). The majority of Women of Reproductive Age, as many as 19 (51.4%), are optimistic about early detection of cervical cancer. The Chi Square test revealed a relationship with a P value of 0.000 between the level of knowledge of women of childbearing age about early detection of cervical cancer and the attitude of carrying out early detection of cervical cancer in the working area of the Pare Health Center.Conclusion: There is a relationship between the level of knowledge of women of childbearing age about early detection of cervical cancer and the attitude of early detection of cervical cancer in the working area of Pare Primary Health Center